Construction of a digital resource information and diagnostic tool for brain diseases - Lau, Cher Chien, 1986-; Mohd. Shahir Shamsir Omar; Fakulti Biosains dan Biokejuruteraan (2012)
Thesis (Sarjana Sains (Biosains)) - Universiti Teknologi Malaysia, 2012